Electrocardiographic predictors of mortality in patients after percutaneous coronary interventions – a nested case–control study. Issue 4 (4th July 2019) - Li, Jin; Wyrsch, Dominic; Heg, Dik; Stoller, Michael; Zanchin, Thomas; Perrin, Tilman; Windecker, Stephan; Räber, Lorenz; Roten, Laurent
Abstract: Background: The outcome of patients undergoing percutaneous coronary interventions (PCIs) varies considerably. Several ECG parameters have recently emerged (PQ interval, P-wave, T-peak-to-T-end interval, T-wave, T/R ratio, J-wave) beyond traditional markers (rhythm, QRS, Q-wave, QT interval, ST segment) and were attributed important prognostic value in the setting of coronary artery disease. The present study integrated for the first time these ECG parameters altogether with the aim to determine their role in predicting patients' outcome after a PCI. Methods: A total of 3342 patients were enrolled in the present study between 2009 and 2013. In a nested case–control design, 644 patients who died within a year post-PCI (cases) were matched 1:4 with patients alive at that particular date (controls). Results: Our data showed that only the presence of a longer QT interval (heart rate-corrected using Bazett formula) was associated with increased risk of death after adjusting for multiple clinical and angiographic risk factors (adjusted OR 1.07; 95%CI 1.01–1.12, p = .022). Conclusion: Our study emphasises the prognostic importance of the QT interval in identifying patients at increased risk of death during the first year after PCI. Clinical Trial Registration – URL: https://www.clinicaltrials.gov . Unique identifier: NCT02241291.